IMPLEMENTATION OF REGIONAL REGULATION NUMBER 3 OF 2016 CONCERNING MANAGEMENT OF WOMEN AND CHILDREN PROTECTION IN HULU SUNGAI UTARA DISTRICT - Sya'bani Arlan, Agus (PPPM STIA Amuntai, 2019)
The increasing number of Divorce each year In Hulu Sungai Utara Regency, this data is obtained based on surveys or direct observations in the Amuntai Religious Court. The number of divorce cases from 2014 was 651 cases, in 2015 it increased to 654 cases, although in 2016 and 2017 it decreased by around 601 and 622 but in 2018 this was only in September as many as 662 cases of this number, so there was an increase in divorce rates. The purpose of this study is to identify and analyze the implementation of Regional Regulations and analyze the obstacles in implementing Regional Regulation No. 3 of 2016 concerning the Protection of Women and Children in the North Hulu Sungai Regency. The research method is qualitative descriptive, type and source of data, namely primary data through observation, interviews while secondary data through data available at the Office of Protection and Empowerment of Women and Children in Hulu Sungai Utara Regency, the technique used in sampling is purposive sampling technique is withdrawal of samples in purpose or can be determined in accordance with the requirements (characteristics, characteristics, characteristics, criteria). The results of the study show that in the implementation of Regional Regulation No. 3 of 2016 concerning the Implementation of Protection of Women and Children in Hulu Sungai Utara Regency, it is still not fully implemented. This can be seen where the handling of these cases has not been fully implemented, then people who are victims of domestic violence or the impact of their divorce is not all that they know about the local regulations, so they have not run properly, efficiently and effectively. So that the firmness in handling the case also cannot be implemented because the sanctions are not mentioned and the contents of the policy need to be renewed. The suggestions given for input include, among other things, providing a place for counseling and complaints about domestic violence issues, especially for the protection of women and children, there must be attention and support from the Hulu Sungai Utara District Head regarding the issue of funding in terms of supporting treatment women's protection case.